The Lepidoptera of Cuatrociénegas Protected Area 1. A new species in the genus Callistege Hübner, [1823] (Erebidae, Erebinae, Euclidiini) from the Chihuahuan Desert, Coahuila, Mexico - Nicholas T. Homziak; David C. Lightfoot; Eric H. Metzler; Kelly B. Miller (ZooKeys, 2021)
A new species of Callistege Hübner, [1823] (Lepidoptera, Erebidae, Erebinae, Euclidiini) is described from Cuatrociénegas Protected Area and Biosphere Preserve in Coahuila, Mexico. Adult male and female moths are illustrated, including genitalia. Callistege clara Homziak & Metzler, sp. nov. is one of 27 new species of insects discovered during an inventory survey of arthropods of White Sands National Monument, USA, and Cuatrociénegas Protected Area (Mexico), funded by the U.S. National Park Service. The Cuatrociénegas Basin is known for high endemism of aquatic and wetland biota within the Chihuahuan Desert. Callistege clara Homziak & Metzler, sp. nov. was found in a wetland environment.